Architecture of the caveolar coat complex - Ludwig, Alexander (2020)
Caveolae are specialized membrane domains that are crucial for the correct function of endothelial cells, adipocytes and muscle cells. Caveolins and cavins are both required for caveolae formation, and assemble into a large (80S) caveolar coat complex (80S-CCC). The architecture of the 80S-CCC, however, has not been analyzed. Here, we study the 80S-CCC isolated from mammalian cells using negative stain electron microscopy and 3D cryo-electron tomography. We show that the 80S-CCC is a hollow sphere with a diameter of 50-80 nm, and so has the same size and shape as individual caveolar bulbs. This provides strong evidence that the distinctive membrane shape of caveolae is generated by the shape of the 80S-CCC itself. The particle appears to be made up of two layers, an inner coat composed of polygonal units of caveolins that form a polyhedral cage, and an outer filamentous coat composed of cavins. The data suggest that the peripheral cavin coat is aligned along the edges of the inner polyhedral cage, thereby providing a mechanism for the generation of a morphologically stable caveolar coat.